Fear of COVID-19, traumatic growth, and traumatic stress symptoms: the mediating role of basic psychological needs - Gargurevich, Rafael; Campodónico, Valeria; Matos, Lennia (Frontiers in Psychology, 2025)
Although COVID-19 brought many negative psychological consequences, many people also experienced psychological growth. The present study investigated why this happened and hypothesized that self-determination theory’s (SDT’s) basic psychological needs (BPNs) may play a role in this explanation. Based on SDT, this cross-sectional study hypothesized that both the satisfaction and frustration of BPNs mediated the associations between fear of COVID-19, post-traumatic growth (PTG), and post-traumatic stress (PTS) symptoms. A sample of 391 Peruvian adults (70.6% women; Mage = 35.04, age range between 18 and 84) responded to several valid and reliable questionnaires: Fear of COVID-19 Scale (FCV.19S); Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS); Impact Event Scale-Revised (IES-R); Post-Traumatic Growth Inventory (PTGI). The results showed that need satisfaction mediated the negative association between fear of COVID-19 and PTG, and need frustration mediated the positive association between fear of COVID-19 and PTG. In addition, a direct effect was found from fear of COVID-19 toward PTS symptoms. The results showed the importance of considering SDT’s BPNs in explaining PTG and PTS after experiencing fear of COVID-19.